THE USE OF WORDS WITH ENGLISH ORIGIN IN UZBEK WEBSITES - Qodirova, Dilnoza; Sadullayeva, Nilufar Azimovna (INTERNATIONAL CONFERENCES, 2023)
The current paper investigates the occurrences of English words on various Uzbek websites. To achieve this, this article has analyzed educational websites, news websites, and the websites of authoritative bodies. The paper gives some preliminary information about the websites investigated and provides a list of the most commonly used English words on these websites.